2008
DOI: 10.3171/jns/2008/109/8/0287
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of infarct formation by brain swelling in a large territorial stroke: a target for neuroprotection?

Abstract: The data indicated that collateral damage caused by the space-occupying effect of a large MCA territory stroke contributes seriously to ischemic lesion formation. The elimination of increased ICP thus must be regarded as a highly neuroprotective measure, rather than only a life-saving procedure to prevent cerebral herniation. Further clinical trials should reveal the neuroprotective potential of surgical and pharmacological ICP-lowering therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 34 publications
1
34
0
4
Order By: Relevance
“…Cerebral edema is a well-recognized factor for high morbidity and mortality in large-territory ischemic strokes. 42 Brain edema following MCA occlusion has been shown to increase gradually over the first 48 hours before peaking. 34 The reduction in brain edema from the early phase may reduce the space-occupying effect and improve regional CBF in the penumbra phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral edema is a well-recognized factor for high morbidity and mortality in large-territory ischemic strokes. 42 Brain edema following MCA occlusion has been shown to increase gradually over the first 48 hours before peaking. 34 The reduction in brain edema from the early phase may reduce the space-occupying effect and improve regional CBF in the penumbra phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oxygen and glucose supply is reduced due to microvascular constriction in response to the depolarization (Dreier et al, 1998;Strong et al, 2007;Luckl et al, 2009). Early formation of vasogenic edema within the first 3 hours is another factor contributing to progressively disturbed tissue perfusion in the penumbra due to mechanical compression of adjacent microvessels and veins in hemispheric experimental stroke in rats (Walberer et al, 2008;Gerriets et al, 2009). CSD alters bloodbrain barrier permeability even in healthy tissue by activating brain matrix metalloproteinases, in particular matrix metalloproteinases-9 (Gursoy-Ozdemir et al, 2004).…”
Section: Malignant Hemispheric Strokementioning
confidence: 99%
“…Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46]. These findings may have been influenced by the "early" timing of craniectomy in their protocols, potentially averting secondary brain damage associated with cerebral edema [47], although the inclusion of patients who may not have truly needed decompression also may have favorably influenced outcome. In contrast, worse outcomes were reported for decompressive craniectomy in traumatic brain injury when compared to maximal medical therapy alone [48].…”
Section: Osmotherapymentioning
confidence: 99%